HUBUNGAN UMUR DENGAN PERUBAHAN PEKERJAAN: SUATU APLIKASI METAANALISIS DALAM UKURAN SAMPEL - Ni Wayan Suriastini (Populasi, 2006)
Meta Analysis is fair statistical technique to integrate results of study have been done. This article integrates studies which explore relationship between age and job changes. This study found correlation value of age and job change over estimate by 4 % and its variance over estimate by 14 % before corrected by sampling error. Outlier of large sample size influences Meta Analysis result. If a study with large sample size has correlation value lower than mean of correlation of the other studies, that study will make the corrected value and variance correlation under estimate.